Isolamento do vírus da raiva em Artibeus fimbriatus no Estado de São Paulo Isolation of rabies virus in Artibeus fimbriatus bat in the State of Sao Paulo, Brazil - Elenice M Sequetin Cunha; Maria do Carmo C S H Lara; Alessandra Figueiredo de Castro Nassar; Miriam M Sodré; Luis Flávio Vani Amaral (Universidade de São Paulo, 2005)
Descrevem-se, pela primeira vez, o isolamento e a identificação do vírus da raiva em morcego frugívoro Artibeus fimbriatus no município de São José do Rio Preto, Estado de São Paulo. O vírus foi isolado de exemplar encontrado em área urbana, caído sob uma árvore e ainda vivo. O diagnóstico foi realizado pelas técnicas de imunofluorescência direta e inoculação intracerebral em camundongos. This is the first report of the isolation and identification of the rabies virus in the frugivorous bat Artibeus fimbriatus in the city of Sao José do Rio Preto, Sao Paulo State, Brazil. The virus was isolated from an animal found in an urban area. The animal was found on the ground under a tree, still alive. Diagnosis was made by direct immunofluorescence and intracerebral inoculation of mice.